HUBUNGAN KADAR DEBU DENGAN FUNGSI PARU PADA PEKERJA PROSES PRESS-PACKING DI USAHA PENAMPUNGAN BUTUT KELURAHAN TANJUNG MULIA HILIR MEDAN TAHUN 2013 - Dunia Terang Sihombing; dr. Halinda Sari Lubis, MKKK; Eka Lestari Mahyuni, SKM, M.Kes (Lingkungan dan Kesehatan Kerja, 2014)
The exposure of  dust in a long time at  work place will cause the heavy stress on organ of respiratory system. The purpose of this research is to know how the correlation of dust concentration with lung function on press-packing process of battered at Tanjung Mulia Hilir Medan 2013. This research is an analytic survey with cross sectional design, which sample are 19 people (total population). Data are analyze by using chi-square test and to know the correlation  using multiple regression logistic test with Backward Stepwise method. The result of research showed that the dust concentration at four point measure at the work place still under the Threshold Limit Value (< 3mg/m3) which are 0.014 mg/m3, 0.007 mg/m3, 0.080 mg/m3 and 0.020 mg/m3. In other hand the lung function shows that 4 workers (20.1%) have disorder and 15 workers (78.9%) are normal. The chi-square test found that the variable of  age, periode of work, a history of lung disease showed has not a significant correlation with lung function. But, the smoking habit and using of PPE has a significant correlation with lung function. Multiple logistic regression analysis  showed that the use of  PPE has more significant correlation with lung function               (p =0.038) than smoking habit. From the result, the worker recommended have to wear personal protective equipment like mask and stop smoking habit to prevent lung function disorder. Keywords :    Dust Concentration, Lung Function, Work Place